Alterações funcionais em artéria mesentérica de ratos com pancreatite aguda - Carvalho, Maria Betânia Trindade (2014)
Acute pancreatitis is an inflammatory process that initiates with the damage of the pancreatic acinar cells and can also involve other organs and peripancreatic tissues. Vascular alterations are proposed as factors that contribute significantly to the morbidity of patients with pancreatitis. However, few studies were directed to understand these alterations and the underlying mechanisms. In this way, the objective of this study was to investigate vascular changes caused by acute pancreatitis induced by common bile duct obstruction (CBDO) on the vascular reactivity of rat mesenteric artery, in order to generate scientific knowledge about the mechanisms involved in this condition and enable future approaches that lead to a better treatment of this disease in humans. For this purpose, adult male Wistar rats were used (220-300 g) and divided into two groups: (i) sham animals, which were submitted to surgery procedure without obstruction of the duct and (ii) CBDO animals which were submitted to surgery procedure and obstruction of the common bile duct. After 24 or 48 h of this surgery, animals were anesthetized and the superior mesenteric artery was removed. Serum samples were also obtained for amylase determination. Mesentery artery rings were obtained (1-2 mm) and used for in vitro reactivity experiments and measurement of nitric oxide (NO) and superoxide anion (O2 -). For the reactivity experiments, the rings were mounted in isolated organ chambers and cumulative concentration-response curves to acetylcholine or phenylephrine were obtained. For evaluating the production of NO and O2 -, rings were incubated with specific fluorescent dyes. Levels of serum amylase were augmented in animals with CBDO after 24 (p<0.05) or 48 h (p<0.001) of obstruction, when compared with sham group, confirming the induction of pancreatitis. Mesenteric rings from CBDO animals showed decreased relaxing response for acetylcholine or contractile response to phenylephrine after 24 or 48 h of induction of pancreatitis, when compared with sham group. Our data also showed an increase in NO (p<0,05) and O2 - (p<0,05) production in the rings collected after 48 h of the surgical procedure, but not after 24 h. These findings showed that acute pancreatitis induction by CBDO impaired relaxation and contractile response, possibly by mechanisms that are triggered by increased NO and O2 - production, probably associated with the inflammatory process. Additional studies are needed to identify the mechanisms underlying these vascular effects of acute pancreatitis.